Promises and Limitations of Neural Stem Cell Therapies for Progressive Multiple Sclerosis. Issue 10 (October 2020) - Pluchino, Stefano; Smith, Jayden A.; Peruzzotti-Jametti, Luca
Abstract : Multiple disease-modifying medications with regulatory approval to treat multiple sclerosis (MS) are unable to prevent inflammatory tissue damage in the central nervous system (CNS), and none directly promote repair. Thus, there is an unmet clinical need for therapies that can arrest and reverse the persistent accumulation of disabilities associated with progressive forms of MS (P-MS). Preclinical research has revealed an unexpected ability of neural stem cell (NSC) therapies to provide neurotrophic support and inhibit detrimental host immune responses in vivo following transplantation into the chronically inflamed CNS. We discuss NSC transplantation as a promising therapy for P-MS, elaborate on the necessities of clinical trial validation and formalized usage guidelines, and caution about unscrupulous 'clinics' marketing unproven therapies to patients. Highlights: Few drugs have been approved for the treatment of progressive multiple sclerosis (P-MS), and those that have are limited in their efficacy to active forms of the disease, and fail to halt degeneration or promote repair and regeneration. State-of-the-art single-cell characterization of the diseased CNS is providing high-resolution insights into deficiencies of endogenous regenerative potential and the shortcomings of animal models of disease. CNS stem cell transplantation has demonstrated encouraging therapeutic potential in preclinical studies of neurological diseases such as P-MS, and there is a growing understanding of the mechanisms of action through which they act on the injured CNS. Comprehensive and well-designed clinical study of CNS stem cell therapies is essential to decisively establish their translational potential and safety, but the marketing of unproven treatments is flourishing in the interim.